Perlindungan Hukum Bagi Merek Terkenal di Indonesia (Studi Kasus Merek Pierre Cardin Perancis Vs Peirre Cardin Jakarta: Putusan Nomor 557 K/PDT.Sus-HKI/2015) - Haryanto, Yulinda Ika Saputra (JIPRO: Journal of Intellectual Property, 2018)
The purposes in this study are to analyze the Supreme Court decision on the cancellation of the trademark PIERRE CARDIN has been appropriate or not by trademark legislation in Indonesia, to assess the legal consequences of the cancellation of PIERRE CARDIN, and to assess potential remedies conducted by Pierre Cardin. This study is a normative empirical legal study. Secondary data consists of primary legal materials in the form of Act No. 15 of 2001 on Trademarks, Law No. 20 Year 2016 regarding Trademarks and IG and the Supreme Court decision No. 557 K / Pdt.Sus-IPR / 2015, while the secondary legal materials in the form of books and scientific journals. While the primary data is conducted by field research. The Supreme Court decision is deciding cases cancellation of the famous mark of PIERRE CARDIN not in accordance with regulations in Indonesia and the norm of international treaties regulating the Famous Mark. Judges tend to be rigid and not digging deeply law. Moreover, Directorate Mark as the parties who participated in trademark infringement less careful in carrying out checks on mere registration, resulting in double registration of the same brand but different owners. Because of law accepted by the brand which canceled its mark is barred from the General Register of Trademarks. The termination of legal protection of the mark is registered. Legal remedies that can be done by Pierre Cardin as the owner of famous brands are apply for Judicial Review, file a new lawsuit, and conduct License Agreement.